Optimalisasi Peran Bawaslu Provinsi Terkait Pencegahan Politik Uang dalam Pemilihan Kepala Daerah - Eka Rika Tumading; Wenly R. J. Lolong (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
The Elections Supervisory Agency (Bawaslu) is a supervisory body tasked with overseeing the practice of money politics during regional head elections. This study examines the authority and oversight mechanisms implemented by Bawaslu in addressing ongoing money politics. Based on the Regional Election Law, Bawaslu has a clear mandate to prevent and verify money politics violations. This law authorizes the election supervisory body to conduct oversight during the campaign and voting period and to impose sanctions on perpetrators of money politics. There is a lack of awareness among the public and regional head candidates regarding the dangers of money politics, which can undermine the democratic order. Therefore, Bawaslu must further tighten its oversight based on statutory regulations to prevent this practice.